2015
DOI: 10.2166/washdev.2015.053
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for VIP latrines in rural Senegal

Abstract: In 2015, African ministers established the Ngor Declaration to achieve universal access to adequate sanitation and hygiene services and eliminate open defecation by 2030. Realizing this target will require significant public and private investment. Over the last two decades, there has been increasing recognition that sanitation programs should be demand driven, yet limited information exists about how much rural residents in developing countries are willing to pay for sanitation improvements. This paper applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In rural Senegal, Hall et al [15] found a household preference for the ventilated pit latrine, and for which households may be willing to pay up to 54,261 FCFA. Though willingness to pay is difficult to compare, each of these studies pertinently shows a willingness by rural households to pay something for improved sanitation, a demographic with limited formal income.…”
Section: Discussionmentioning
confidence: 99%
“…In rural Senegal, Hall et al [15] found a household preference for the ventilated pit latrine, and for which households may be willing to pay up to 54,261 FCFA. Though willingness to pay is difficult to compare, each of these studies pertinently shows a willingness by rural households to pay something for improved sanitation, a demographic with limited formal income.…”
Section: Discussionmentioning
confidence: 99%
“…While households traditionally bear a large portion of water and sanitation investments, it is important to note that willingness-to-pay (WTP) for sanitation is often low among low-income households. Prior studies have investigated demand among poor households for a range of sanitation products and services, including latrine slabs, , onsite sanitation facilities, , connections to sewer networks, , professional pit emptying services, , and container-based sanitation (CBS). , These studies have consistently found that WTP among low-income households is well under the market prices of sanitation products and services. Similarly, the 2016 World Bank report warned that safe sanitation services are likely unaffordable to the urban poor .…”
Section: Introductionmentioning
confidence: 99%
“…Combined, the results of these studies suggest that residents of developing countries are willing to pay between 0.1 and 1.8 per cent of their annual income to improve their municipal solid waste management systems. 1 Additional stated preference studies suggest that individuals in low income countries also value improved wastewater services (Birol and Das, 2010;Ndunda and Mungatana, 2013;Hall et al, 2015;Laré-Dondarini, 2015) and are willing to pay up to as much as 2 per cent of their annual incomes for connections to wastewater management systems (Seraj, 2008). While many studies have estimated the willingness to pay for sanitation services, they have done so using stated preference methods (e.g., contingent valuation).…”
Section: Willingness To Pay For Sanitation Services: a Literature Reviewmentioning
confidence: 99%